2014
DOI: 10.1186/2048-7010-3-15
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surrounding crop and semi-natural vegetation on the plant diversity of paddy fields

Abstract: Background: The ecosystems around, and plant composition in, paddy fields in Java are varied, owing to differences in climate, altitude, and traditional farming practice. This study examines the effects of different types of surrounding land use and vegetation on the plant diversity in paddy fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In our study, no live nymphs of any instar, or T. limbativentris oviposition were found in any of the recorded host plants, not even in the winter rice sprouts found in grassland. This agrees with previous winter studies that involved individuals of T. limbativentris in imaginal diapause (Klein et al, ; Kruger, ). This suggests that the winter host plant selection by T. limbativentris may be related more to plant characteristics that ensure a good refuge than to the characteristics of the plants that facilitate reproduction/performance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, no live nymphs of any instar, or T. limbativentris oviposition were found in any of the recorded host plants, not even in the winter rice sprouts found in grassland. This agrees with previous winter studies that involved individuals of T. limbativentris in imaginal diapause (Klein et al, ; Kruger, ). This suggests that the winter host plant selection by T. limbativentris may be related more to plant characteristics that ensure a good refuge than to the characteristics of the plants that facilitate reproduction/performance.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the higher abundance of T. limbativentris on grassland vegetation in relation to the rice stubble could be associated with the hostile habitat offered by the rice plots during the post‐harvest time (dry, high humidity, destruction of habitat, among others). These are unfavourable conditions for stink bug survival, and in these conditions, the population moves to areas near the rice plots, with more favourable habitats for hibernation (Ferreira et al, ; Kruger, ; Pazini et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies suggest that high natural plant biodiversity can positively contribute to agroecosystem productivity by enhancing natural pest biocontrol, because native vegetation can host natural enemies of crop pests which may assist natural regulation of pest outbreaks (Tscharntke et al ., 2007; Haddad et al ., 2011). Because of this role, many recent studies have concluded that conserving natural plant biodiversity around agricultural systems plays a positive function in helping to maintain crop health (e.g., Garbach et al ., 2014; Kumalasari and Bergmeier, 2014; Luo et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, lowland rice systems in Java have greater rice weed diversity compared to upland ecosystems (Kumalasari and Bergmeier, 2014); however, to our knowledge, there has been no work characterising differences in wheat weed communities within farms located in either an upland versus lowland topography.…”
Section: Introductionmentioning
confidence: 99%